2011
DOI: 10.15835/nsb315597
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Two Monogenean Parasites on Different Length Groups of Crucian carp (Carassius carassius Linneus, 1758)

Abstract: Dactylogyrus anchoratus Dujardin, 1857 and Gyrodactylus katharineri Malmberg, 1964 were identified on crucian carp, Carassius carassius L., 1758 in the present study, which was carried out between February 1999 and January 2000. A total of 117 fish specimens were examined. The infestation prevalence and mean intensity levels for G. katharineri was 37.61%, respectivly 27.75±2.203 and for D. anchoratus was 24.78%, 4.69±1.730 per fish, respectively. The infestation prevalence and mean intensity levels were highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…al. 2002); in Alburnus alburnus from the Enne Dam Lake (Koyun & Altunel 2007); in Squalius cephalus from the Akçay Stream (Öztürk 2014); in Barbus lacerta and Oxynoemacheilus tigris from the Murat River (Koyun et.al. 2015(Koyun et.al.…”
Section: Biogeographic Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…al. 2002); in Alburnus alburnus from the Enne Dam Lake (Koyun & Altunel 2007); in Squalius cephalus from the Akçay Stream (Öztürk 2014); in Barbus lacerta and Oxynoemacheilus tigris from the Murat River (Koyun et.al. 2015(Koyun et.al.…”
Section: Biogeographic Assumptionsmentioning
confidence: 99%
“…Of these the genus Allocreadium is represented by only two species. Allocreadium isoporum (Looss 1894) Looss, 1902 was described from nine freshwater fish species in Turkey (Aydogdu et al 2002;Koyun & Altunel 2007;Öztürk 2014;Koyun et al 2015Koyun et al , 2016Aydogdu et al 2018), whereas A. lobatum Wallin, 1909 was recorded only from Blicca bjoerkna in the Sakarya River by Akmirza and Yardimci (2014). In recent phylogenetic studies nine valid species of Allocreadium have been confirmed: A. isoporum, A. lobatum, A.…”
Section: Introductionmentioning
confidence: 99%
“…This would lead to the prediction that there are well over 23,250 monogenean species; however, less than 4,000 species have been described worldwide (Chisholm and Whittingtonn, 1998). To date, there have been many studies on monogenean parasites in Turkey (Özer et al, 2004;Özer and Öztürk, 2005;Öztürk and Altunel, 2006;Soylu and Emre, 2007;Soylu, 2009;Koyun, 2011;Koyun and Altunel, 2011;Öztürk, 2011;Akmırza, 2013). On the other hand, there is no parasitological study of fishes in Lower Kızılırmak Delta in Turkey.…”
Section: Introductionmentioning
confidence: 99%